2005
DOI: 10.1136/jnnp.2005.065417
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between impulsive sensation seeking traits, smoking, alcohol and caffeine intake, and Parkinson's disease

Abstract: This study raises the possibility that there is a neurobiological link between low sensation seeking traits--which might underlie the parkinsonian personality--and the hypothetical protective effect of cigarette smoking and caffeine consumption on PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(134 citation statements)
references
References 40 publications
4
124
0
4
Order By: Relevance
“…A study conducted in Singapore reported an inverse association between alcohol intake as a continuous variable and PD (p value 0.001) [358]. Two studies reported decreasing risk of PD with increasing amount of alcohol intake, although comparisons between categories of alcohol intake were generally non-significant [417,458]. One relatively large (342 cases) German study observed risk estimates below unity for beer and spirits, but not for wine [458].…”
Section: Case-control Studiesmentioning
confidence: 99%
“…A study conducted in Singapore reported an inverse association between alcohol intake as a continuous variable and PD (p value 0.001) [358]. Two studies reported decreasing risk of PD with increasing amount of alcohol intake, although comparisons between categories of alcohol intake were generally non-significant [417,458]. One relatively large (342 cases) German study observed risk estimates below unity for beer and spirits, but not for wine [458].…”
Section: Case-control Studiesmentioning
confidence: 99%
“…Both associations might be correct and are consistent with a unifying explanation involving contrasting behavioural characteristics of the two conditions: ie, patients with Parkinson's disease may lead a conservative lifestyle Á avoiding smoking, alcohol, coffee etc. [23 Á 26] Á while those with MS may do the opposite Á that is they have 'impulsive seeking traits' leading to health adverse conduct [26,27]. This proposition could be tested by a case-control questionnaire or, better still, by a prospective cohort study.…”
Section: Combinedmentioning
confidence: 99%
“…brza vožnja automobila ili ekstremni sportovi) [3,16]. Pobrojane karakteristike su inače suprotne klasičnom, anhedoničnom profilu ličnosti koji je označen kao dominantan kod oboljelih od Parkinsonove bolesti, s obzirom na manju učestalost pušenja, upotrebe alkohola ili kafe od učestalosti ovih pojava u opštoj populaciji [25]. Konačno, moguće je da i kulturološke osobenosti i različite socijalne norme imaju značajan uticaj na učestalost patološkog kockanja, s obzirom da je prevalencija ovog poremećaja značajno manja kod oboljelih od Parkinsonove bolesti u Kini i Koreji (0,32% i 1,3%) [26,27], zemljama u kojima su mogućnosti za kockanje limitirane.…”
Section: Učestalost I Faktori Rizikaunclassified